2015
DOI: 10.1016/j.ijdevneu.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tactile stimulation decreases depression‐like and anxiety‐like behaviors and potentiates sertraline action in young rats

Abstract: It is well known that events which occur in early life exert a significant influence on brain development, what can be reflected throughout adulthood. This study was carried out in order to assess the influence of neonatal tactile stimulation (TS) on behavioral and morphological responses related to depression-like and anxiety-like behaviors, assessed following the administration of sertraline (SERT), a selective serotonin re-uptake inhibitor (SSRI). Male pups were submitted to daily TS, from postnatal day 8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
2
24
1
Order By: Relevance
“…Taking into account the reduction in CORT levels and the behavioral results obtained in EPM and DBT, we can state that TS is able to reduce emotionality, anxiety and fear‐like symptoms during adult life by regulating HPA axis activity. These results are in accordance with a recent study by our laboratory in which TS has shown its beneficial effect by reducing CORT and cortisol, which are regulated in the same way and simultaneously released in animals submitted to a depression‐like protocol (Freitas et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account the reduction in CORT levels and the behavioral results obtained in EPM and DBT, we can state that TS is able to reduce emotionality, anxiety and fear‐like symptoms during adult life by regulating HPA axis activity. These results are in accordance with a recent study by our laboratory in which TS has shown its beneficial effect by reducing CORT and cortisol, which are regulated in the same way and simultaneously released in animals submitted to a depression‐like protocol (Freitas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these outcomes would support the hypothesis of a better regulation of anxiety behaviors through high GR immunocontent in the hippocampus as suggested by Sampedro‐Piquero et al (). Considering these findings, we can confirm that TS is able to mimic anxiolytic and antidepressant drug effects as recently shown (Boufleur et al, ; Freitas et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, BDNF is involved in the origin of depression and in antidepressant effects and NTS enhanced BDNF ( Martinowich et al, 2007 ; Antoniazzi et al, 2017 ). Next, NTS decreased depression-like behavior later in life ( Freitas et al, 2015 ): TS early in life was accompanied by an increase in active swimming time and a decrease in immobility time in FST. Handling in animals resulted in different behavioral, endocrinological and neurochemical adaptive responses, suggesting the involvement of various neural pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal TS enriches the experience and improves maturation of newborn animals, positively influencing behaviors and neuroendocrine systems in pups ( Boufleur et al, 2012 , 2013 ; Antoniazzi et al, 2014 ). Others showed that neonatal TS increases neurogenesis and neuroplasticity, improves anxiety-like behaviors and prevents depression-like behaviors ( Richards et al, 2012 ; Freitas et al, 2015 ; Roversi et al, 2019 ). Recent reports have shown that when TS is applied both during the initial periods of development and in adult rats, neurotrophins such as brain-derived neurotrophic factor (BDNF) and fibroblast growth factor 2 (FGF-2) increase in different brain areas.…”
Section: Introductionmentioning
confidence: 99%